2024
DOI: 10.3847/1538-4357/ad3faf
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the X-Ray Polarization of the Black Hole Transient Swift J1727.8–1613 during a State Transition

Adam Ingram,
Niek Bollemeijer,
Alexandra Veledina
et al.

Abstract: We report on an observational campaign on the bright black hole (BH) X-ray binary Swift J1727.8–1613 centered around five observations by the Imaging X-ray Polarimetry Explorer. These observations track for the first time the evolution of the X-ray polarization of a BH X-ray binary across a hard to soft state transition. The 2–8 keV polarization degree decreased from ∼4% to ∼3% across the five observations, but the polarization angle remained oriented in the north–south direction throughout. Based on observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 117 publications
0
0
0
Order By: Relevance
“…Combined with the submillimeter band observation, these results indicate that the corona is elongated orthogonal to the jet. Similar accretion geometry was also proposed in the hard state by Ingram et al (2024) and Podgorný et al (2024). As the outburst evolves, Svoboda et al (2024) found that the polarization degree decreases dramatically to 1% in the soft state, which suggested that the polarization is mainly contributed by the upscattered radiation in the hot corona.…”
Section: Discussionsupporting
confidence: 68%
“…Combined with the submillimeter band observation, these results indicate that the corona is elongated orthogonal to the jet. Similar accretion geometry was also proposed in the hard state by Ingram et al (2024) and Podgorný et al (2024). As the outburst evolves, Svoboda et al (2024) found that the polarization degree decreases dramatically to 1% in the soft state, which suggested that the polarization is mainly contributed by the upscattered radiation in the hot corona.…”
Section: Discussionsupporting
confidence: 68%
“…Radio observations from the Submillimetre Array (SMA), the Karl G. Jansky Very Large Array, the enhanced Multi Element Remotely Linked Interferometer (eMERLIN), and the Allen Telescope Array (ATA) showed a bright, flat-spectrum, unresolved source (Baglio et al 2023;Miller-Jones et al 2023;Vrtilek et al 2023;Williams-Baldwin et al 2023). Polarization observations at X-ray wavelengths with the Imaging X-ray Polarimetry Explorer (IXPE), at optical wavelengths with the 60 cm Tohoku telescope, at 230 GHz with the SMA, and at 5.5 and 9 GHz with the Australian Telescope Compact Array (ATCA) revealed J1727 to be polarized across the electromagnetic spectrum, with a position angle consistent with being aligned in the north-south direction (Dovciak et al 2023;Ingram et al 2023;Kravtsov et al 2023;Veledina et al 2023;Vrtilek et al 2023). These observations suggested that J1727 had a bright, compact, hard-state jet aligned in the north-south direction.…”
Section: Introductionmentioning
confidence: 99%